Islam and Muslim in multi religious society: realities and challenges in Sabah, Malaysia - Amir, S.; Suliaman, I.; Abd Razzak, M.M.; Mohd Yusoff, Mohd Yakub @ Zulkifli; Abdullah, M.; Ahmad Shah, F.; Deraman, F.; Ahmad, K.; Mohd Noor, M.M.; Touhami Meftah, J.; Ariffin, S.; K. Kassar, A.; et al. (© IDOSI Publications, 2013, 2013)
One of the sources says that Islam has come to Malay World in eleventh century of Masihi and this is supported by the discovery of gravestone in Champa, Gresik Java as well as Kedah together with the discovery of stone monument in Terengganu dated 1303 Masihi. This situation is exposing the phenomenon of Islam’s growth in the Peninsular Malaysia earlier from the Borneo Isle where it has been receiving Islam during the 15th century of Masihi intermediated by al-Makhdum. Thus, this argumentation is at least influencing the history and the situation of Islam’s development of the Borneo especially in Sabah amongst the native people. Nevertheless it is indisputable if we assumed that the empirical battle to authorize religion of Islam from the Peninsular Malaysia has empower an inducement towards the local fundamentalists to accentuate the Islamic spiritual da’wah at Sabah until Islam has been the official religion of the state. Hence, from the prepared revision and analytical reflection, we shall examine and explore the history as well as the growth of Islam’s prospect especially at Sabah by considering the aspect of Islamization reality and current religious activities including Christianization. We also explore the development’s factors, institution and also the person in authority towards this issue. It is adequate to highlight that Islam’s nuance at Sabah, which situated in the north of Borneo Isle, is multi-dimensional in its characteristic, which is in itself is a unique state in the country.